CRITICAL REVIEW OF METHODS FOR EVALUATING ACOUSTIC CHARACTERISTICS OR PREMISES - R. S. Fediuk; A. V. Baranov; R. A. Timokhin (Вестник СибАДИ, 2020)
Introduction: The development of effective structural materials with improved acoustic characteristics is relevant for the modern construction industry. Considering the variety of international building standards for acoustic insulation and soundproofing of buildings, it is essential to systematize the modern methods of studying these characteristics. The purpose of the study was a comprehensive review of methods for determining acoustic characteristics in construction, as well as an analysis of literature and international standards to improve the health and comfort of the urban population.Main part: Due to the variety and complication of the study of the acoustic characteristics of buildings, premises and individual walling, the article provides an analysis of methods for evaluating these characteristics. The limitations on the size of rooms and sound frequencies for measuring reverberation time have been identified. The process of improving the method of measuring acoustic impedance in Kundt’s tube is shown. The methodology for determining the numerical parameters of sound insulation in buildings using the study of building envelopes taking into account the spectra of various noise sources located inside and outside the building is considered in detail. It was found that existing methods for measuring impact noise show poor reproducibility in the low frequency range. The analysis of the works proved that the sound reflection characteristics theoretically depend on the thickness and rigidity of the reflecting surface and its surface density.Conclusions: The scope of building materials with improved acoustic characteristics is quite extensive. Further research may be aimed at improving methods for studying the characteristics of sound absorption and sound reflection.Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.